Routine for cleaning and maintaining spectacle among regular spectacle wearers - Yadav, Rakesh Kumar; Rani, Anjali (International Journal Of Community Medicine And Public Health, 2022)
Background: The objective of the study was to evaluate routine for cleaning and maintaining eyewear among regular spectacle wearers. Methods: The observation questionnaire-based study was conducted among 170 students who has visited our university ophthalmology OPD. The selected participants were asked to response to a pretested, pre validated questionnaire related to routine for cleaning and maintaining eyewear via goggle form over a period of 6 months. The written consent was taken from each participant prior to enrolled for the study. Results: of total 170, 30% participants were male and 70% were female with mean age of 21.06±2.10 years. 39% participants were using spectacle for 2-5 years. 63.53% participants were prescribed spectacle to correct refractive error. 90% participants responded that they used to clean their glasses regularly. 61.76% responded that they used to wear spectacle by holding with both hands. 45.29% used to remove their spectacle by holding the spectacle at temple with one hand which is wrong way. 44.12% responded that they clean their glasses when needed while 35.88% clean their glasses before use and 20% participants clean their glasses before and after use. Conclusions: Inadequate knowledge about the wearing/removal or handling techniques, cleansing and maintenance of eyewear were found even in the prolonged spectacle user. Proper instructions about the spectacle performance, repair and regular follow up should be provided to the patient. Counselling by the optician, optometrist or ophthalmologist at the time of prescribing eyeglasses can possess better understanding among the eyeglass’s wearers.